Association of Morbidity with Extent of Resection and Cavernous Sinus Invasion in Sphenoid Wing Meningiomas - Ivan, Michael E. (Thieme Medical Publishers, 2012)
Sphenoid wing meningiomas (SWMs) typically are histologically benign, insidious lesions, but the propensity of these tumors for local invasion makes disease control very challenging. In this review, we assess whether the degree of resection and extent of cavernous sinus invasion affects morbidity, mortality, and recurrence in patients with SWM. A comprehensive search of the English-language literature was performed. Patients were stratified according to extent of resection and extent of cavernous sinus invasion, and tumor recurrence rate, morbidity, and mortality were analyzed. A total of 23 studies and 131 patients were included. Overall recurrence and surgical mortality rate were 11% and 2%, respectively (average follow-up = 65 months). Cranial nerve III palsy was significantly associated with incompletely versus completely resected SWMs (7 to 0%) as well as meningiomas with cavernous sinus invasion versus no sinus invasion (14 vs. 0%). No significant difference in tumor recurrence rate was noted between these groups. In conclusion, complete excision of SWMs is always recommended whenever possible, but surgeons should acknowledge that there is nonetheless a chance of recurrence and should weigh this against the risk of causing cranial nerve injuries.